Facial Height and Its Effect by Tooth Wear, Age and Sex Assessed By Soft Tissue Analysis - Pandey, Anisha; Bhattarai, Rosina; Shrestha, Suraksha (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Tooth wear is one of the major and widely accepted problem nowadays. It is the loss of dental hard tissues by these processes: attrition, abrasion and erosion. It can occur due to various factors such as abnormal tooth contact, abrasive dental hygiene habits and erosive dietary factors. Methods Full face photographs of each subject was taken from the frontal view with a natural head position guided to true horizontal in 66 sample. All photographs were evaluated for consistency in head position and picture quality. Total facial height was subdivided into two components: upper facial height and lower facial height. Measurements of UFH and LFH and their ratio were recorded. Also tooth wear was assessed on a tooth-by-tooth basis rated according to the 5-point ordinal scale (0-4). All the data was statistically analyzed by SPSS. Results Statistically significant difference was found between Lower Facial Height and age group (p-value=0.02) whereas there was no statistically significant difference between UFH and RUL with age group. UFH and LFH was found to be slightly higher in females than males, however, on application of independent t-test it was found that there were no statistically significant differences between gender and facial height (p-value > 0.05). Weak negative correlation was found between facial height, age and tooth wear (r=-0.24, p-value 0.052 and r-value =-0.28, p-value 0.023). Conclusions Facial height decreases with increase in age. Upper facial height is slightly greater than lower facial height with tooth wear.